Perancangan Game Kasada Aksara Dan Bahasa Sunda Sebagai Media Edukasi Menggunakan Unity Berbasis Android - Didin Rudini; Ade Bastian; Dadan Zaliluddin (J-ENSITEC, 2023)
The utilization of information technology as an educational medium is one of the efforts that can be chosen to preserve the Sundanese script and language because it is very relevant to modern times like now. Educational media in the form of Android-based Games can be a means of entertainment as well as provide information about the Sundanese script and language, besides that it is effortless to access because it is enough to use a device that uses the Android operating system. The type of Game chosen is a puzzle Game and a Game of arranging letters into words so that it can train the memory and accuracy of the users of this Game. The Game interface design process uses the Figma application and Adobe Illustrator, then the Game design process uses the Unity application. It is utilizing Android-based Games as educational media will provide a more enjoyable and flexible learning experience.